The drivers of energy-related financial hardship in Australia – understanding the role of income, consumption and housing. (January 2019) - Nelson, Tim; McCracken-Hewson, Eleanor; Sundstrom, Gabby; Hawthorne, Marianne
Abstract: Saunders and Bedford (2017) demonstrated that income levels are inadequate for some Australian households to maintain a basic standard of living. Analysing utility bills can extend this consideration of income adequacy issues given the essential nature of services such as electricity, telephony and water. This article builds on the work presented by Simshauser and Nelson (2014) about key demographic cohorts in Australia that have a high incidence of energy-related financial hardship. Our analysis indicates that energy related financial hardship is likely to be related to a combination of the following: family formation demographics; low-income (often reliant upon government income support); higher household size; and higher than average consumption. Our policy recommendations are relatively straightforward: development of tools to allow easier 'shopping around' by energy customers; cessation of credit-checking by energy retailers as a means of restricting access to energy offers; reform of state-based concessions frameworks; a lifting of income support for some key cohorts (e.g. unemployed); improvements to energy-efficiency standards; and amendments to tenancy laws to overcome potential principal-agent issues associated with uptake of new energy products and services such as embedded solar PV and battery storage. Highlights: This article builds on Simshauser and Nelson (2014) . We examine causes of energy related financial hardship. We establish four policy recommendations.